2013
DOI: 10.22401/jnus.16.3.21
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion Coefficients of Different Types of Liquid Environments Into Binary Polymer Blend

Abstract: In this study, unsaturated polyester resin (UPE) and Natural rubber (NR) were used to prepared binary polymer blend (UPE/ NR) with weight ratio (95/5) %. The present paper investigates the diffusion behavior of three environmental groups , the first group is different types of water included (distilled water, tap water, rain water), the second is diluted solutions with same concentration (HCl , H2SO4, NaCl) and the third is solvents (ethanol, kerosene, benzene) and study their effects through (UPE/NR) polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…6 shows the acetic acid diffusion in PVC, and PVC loading with SiO 2 . The results proved that for SiO 2 /PVC there was increasing in swelling and till they were more than (PVC) Figure 6illustrated that there was unsystematic changes of weight gain with SiO 2 loading ratios, but at 10%SiO 2 /PVC was of the lower absorption [22,23].…”
Section: The Diffusion Studies Of Different Types Of Liquid Environmementioning
confidence: 74%
See 3 more Smart Citations
“…6 shows the acetic acid diffusion in PVC, and PVC loading with SiO 2 . The results proved that for SiO 2 /PVC there was increasing in swelling and till they were more than (PVC) Figure 6illustrated that there was unsystematic changes of weight gain with SiO 2 loading ratios, but at 10%SiO 2 /PVC was of the lower absorption [22,23].…”
Section: The Diffusion Studies Of Different Types Of Liquid Environmementioning
confidence: 74%
“…7 it was observed that unsystematic changes in weight gain by SiO 2 loading that reflected by the existence of some voids, and cracks after all cases especially with (NaOH). These defects may be related to penetrate of this solution into the structure of polymer systems more than the other liquids under work [22]. Fig.…”
Section: Sodium Hydroxide Absorption In Pvc and Its Compositesmentioning
confidence: 96%
See 2 more Smart Citations
“…Polymer blends have become very important subject for scientific investigation in recent years because of their growing commercial acceptance, and they can possess unusual combinations of properties [1,2].…”
Section: Introductionmentioning
confidence: 99%